Current issues of pedagogy and psychology - Prokopev N. I., Ananev V. N., Ponomareva L. I., Gurtovoi E. S., Novoselov K. A., Orekhova S. E., Sivak O. A., Shevtsova A. V., Kudriashova S. K., Kudriashov V. I., Gamalienko A. B., Saenko N. V., Piatibratova I. V., Iakusheva O. V., Aleksina T. V., Aleksandrov S. G., Zenkina V. G., Solodkova O. A., Bozhko G. G., Agibalova A. A., Andreeva O. S., Koreneva A. V., Veretennikova N. D., Koreneva A. V., Kalmykov V. A., Ladukhina N. R., Iagudin V. S., Arzamasova E. L., Gani S. V., Konstantinova N. I., Glotova G. A., Shipilova E. S., Krasnova S. G., Kachalov V. I., Stepanov A. N., Kharlamova K. E. (Current issues of pedagogy and psychology, 2025)
the chapter analyzes the accumulated experience in the use of problem-based learning (PBL), examines the main advantages and disadvantages of PBL, proposes an option for organizing a clinical lesson in the form of a problem seminar and the most suitable way to assess the knowledge gained, determines the prospects for further improving teaching and assessing knowledge in the study of clinical disciplines.
Keywords: педагогика; медицинское образование; проблемно-ориентированное обучение; problem-based learning; medical education; обучение клиническим дисциплинам; суммативное оценивание знаний; pedagogics; training in clinical disciplines; summative knowledge assessment